Context Assessment for Agroecology Transformation in the Tunisian Living Landscape - Alary, Veronique; Frija, Aymen; Ouerghemmi, Hassen; Idoudi, Zied; Rudiger, Udo; Rekik, Mourad; Souissi, Asma; Dhehibi, Boubaker; Bahri, Haithem; Mekki, Insaf; Toukebri, Wael; Barbouchi, Meriem; et al. (International Center for Agricultural Research in the Dry Areas, 2022)
The purpose of this Context Assessment is threefold: first, to characterize the environmental, social and economic and political contexts of the Tunisian ALL; second, to understand the data and information currently available in sub-region of the ALL, and third to characterize the extent to which agroecological principles are already being employed locally at the ALL levels. This report constitutes a basis of information and discussion to conduct the impact assessment. It is also valuable to all WPs in the Initiative as it provides critical quantitative or qualitative data and information regarding capacities assessment, policy influence, and other environmental attributes which can guide the initiative implementation and impact in 2023/2024. The present Context Assessment in Tunisia has been elaborated from primary and secondary sources of data. The primary sources of data are issued from focus groups and formal and informal interviews conducted in the targeted area between June and December 2022, as part of WP1 and WP4 activities. The secondary sources of data came from previous research and development projects, in addition to formal and grey literature or technical reports and policy documents. This report will be enriched with a household survey planned during the first quarter of 2023. This report contributes to Output 2.1. Baseline – current conditions of agricultural systems of small holder farmers in each ALL, Output 1.1 on establishment of the ALL, Output 4.1 on the identification of policies and local institutions and their role in the AE pathways.